Description of the second species of Synhalcurias Carlgren, 1914, Synhalcurias kahakui sp. nov. (Actiniaria: Actinernidae) with redescription of S. elegans (Wassilieff, 1908) - Izumi, Takato; Yanagi, Kensuke (Zootaxa, 2021)
We describe a new sea anemone species, Synhalcurias kahakui sp. nov., from specimens collected off Otouto-jima and Amami-oshima islands in July 2016 and May 2019. respectively. These sea anemones were identified as belonging to family Actinernidae due to their many endocoelic perfect mesenteries and identified as belonging to the genus Synhalcurias Carlgren, 1914 because they have an oral disc without any developed lobes. Though this genus presently accommodates only one species, Synhalcurias elegans (Wassilieff, 1908), our specimens are smaller than the aforementioned species, have fewer mesenteries, lack nematocyst batteries on the column, and have two types of microbasic p-mastigophores on the mesenterial filaments. These specimens are described as Synhalcurias kahakui sp. nov. In view of the new species, the diagnosis of genus Synhalcurias is revised. In addition, we redescribe S. elegans based on newly specimens collected from Japan.